Landscape ecology and environmental quality of forest remnants in Atibaia River sub-basin covering the municipality of Campinas, SP - Silva, Alessandra Leite da [UNESP]; Longo, Regina Marcia (Centro Pesquisas Florestais, Ufsm, 2020)
Forest fragmentation is one of the factors which interfere in the sustainability of natural resources, biodiversity and life quality. In view of this, studies that assess the quantitative and qualitative environmental properties of a given ecosystem and/or landscape are essential. Therefore, the analysis of landscape ecology acts effectively. Thus, the present study aimed to evaluate, based on landscape metrics, the quality of the forest remnants presents in the Atibaia river sub-basin covering the municipality of Campinas / SP. For that, the following metrics were used: Size; Central Area Index; Circularity Index; Distance from the Nearest Neighbor; Proximity to the Watercourse; Water Production; Degree of Land Use and Occupation in the Surroundings and Degree of Soil Erodibility. These were analyzed individually and through the Environmental Quality Index (IQ(rem)). There was a high degree of forest fragmentation, given by the high number of remnants, especially small and with a low representative central area, however, located close to each other. In addition, as this watershed is a water-producing for supply, the need for specific conservation strategies for these remnants is emphasized, in order to guarantee water production in quantitative and qualitative terms.
Keywords: Landscape metrics; Forest fragmentation; Green infrastructure